Demonstrações contábeis aplicadas ao setor público: um estudo de conformidade a luz da norma brasileira de contabilidade aplicada ao setor público - Nunes, Roberlânia Maria de Oliveira (Universidade Federal Rural do Semi-Árido, 2017)
The objective of this study was to analyze the level of compliance between the accounting frameworks disclosed by Brazilian capitals and the structures required by the Public Sector Accounting Manual (MCASP). Based on the financial statements published in the years 2014 and 2015. The collection instrument was composed of 97 items, distributed in the six financial statements and in the explanatory notes, according to the need for analysis in each statement. It was verified at the end of the research, that in 2014, the compliance percentage was 51.12%. In 2015, this percentage grew by 16.2%, reaching a result of 67.32% of compliance in the period. The North Region, in 2014, achieved the highest level of compliance, reaching 62.48%. In 2015, the one who achieved the highest level of compliance was the Southeast region with a result of 73.84% compliance. Among the capitals the best result was that of Palmas, in 2014, with 82.70% of conformities in its demonstrations. And in 2015, it was Fortaleza with a compliance level of 84.52%. The accounting statement with the highest compliance in 2014 and 2015 was the Budget Balance Sheet, with a compliance percentage of 87.5% in 2014 and reaching a compliance rate of 96.25% in 2015. The Statement Of the Mutations in Shareholders' Equity (DMPL), was the least disclosed among the capitals, which generated a low percentage of compliance. In 2014, the only capital that disclosed to DMPL was Palmas. In the year 2015, DMPL was announced by the capitals: Boa Vista, São Paulo and Florianópolis
Artigo
Keywords: Processo de Convergência; Norma Brasileira de Contabilidade Aplicada ao Setor Público; Demonstrações contábeis; Conformidade; Convergence Process; Brazilian Standard of Accounting Applied to the Public Sector; Accounting statements; Conformity; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::CIENCIAS CONTABEIS